The Role of Vocal Fold Bowing on Cough and Swallowing Dysfunction in Progressive Supranuclear Palsy - ENVER, NECATİ (WILEY, 2021)
Objectives: Progressive supranuclear palsy (PSP) is a neurodegenerative disease which results in cough and swallowing dysfunction and aspiration pneumonia. Relationships among vocal fold atrophy, cough, and swallowing have been identified in related diseases, but remain unknown in PSP. This study examined: 1) the prevalence of vocal fold bowing in PSP, and 2) the influence of vocal fold bowing on cough and swallowing in PSP. Study Design: Prospective Cohort Study. Methods: Twenty-three participants with PSP completed instrumental assessments of cough and swallowing. Vocal fold bowing (BI) and swallowing safety (PAS) was assessed using flexible laryngoscopy. Measures of cough effectiveness were obtained using spirometry. Statistical analyses were used to determine the frequency of mild-moderate (BI > 0) and severe (BI > 12.2) bowing, and to assess the influence of BI on PAS and cough effectiveness in PSP. Results: Fifty-two percent (n = 12) of participants exhibited severe bowing while 48% (n = 11) exhibited mild-to-moderate bowing. Voluntary cough peak expiratory flow rate (P= .01), as well as reflex (P= .02) and voluntary (P= .005) cough volume acceleration were lower for participants with severe BI when compared to mild-to-moderate BI. However, BI did not influence PAS (P> .05). Conclusions: Findings from this study suggest that vocal fold bowing is highly prevalent in PSP and associated with reduced reflex and voluntary cough effectiveness. These findings provide insight into the pathophysiology of compromised airway protection in this patient population. Future studies should examine vocal fold atrophy as a treatment target for behavioral and medical intervention in PSP.
Keywords: Progressive supranuclear palsy; aspiration; cough; vocal fold atrophy; bowing index; laryngoscopy; ABNORMALITIES; DYSPHAGIA